The influence of country image components on Malaysia consumers toward the perceptions of American products - Muhammad Firdaus, Shahidan (2014)
The objective of this study is to examine the relationship between country image and product country image toward the willingness to buy of US products in the context of Malaysia consumers’. The country image divided to affective and cognitive component (i.e. competence, warmth, admiration and contempt). A survey questionnaire was used in order to obtain the feedback from the respondent. Samples of this study were students from University Utara Malaysia and hence, total of 230 valid questionnaires were gathered and analyzed using SEM approach. The result shows that the affective component of country of image has a direct relationship with its consumers’ willingness to buy US products while the cognitive component does not relate to the willingness to buy. This study contributes to both the literature as well as practitioners, on the critical antecedents that help firms to understand consumers’ perception toward American products in the effort of capturing Malaysia’s market.